Influence or Tillage Methods and Mulches on Soil Moisture and Yield of Gram and Wheat Under Rainfed Condition - Khan, M A (Annals of Arid Zone, 2016)
Influcnce of tillage methods in aSSOClallon wilh mulches was studied on the conservation of sail moisture, it- utilization and Ihe yield of gram and wheat crops raisad on a vertisol under rainfed condition. In gram. subsoiling + gypsum. and sub-soiling + saw dust treatments, respectively, retained soil moisture 175 to 21 5% and 16 to 20% higher than light harrowing wing + no mulch, and no-tillage + no mulch treatments. [n wheat, soil moisture was 9.4 to 9.9% and 8.2 to 8 8% higher under deep ploughing + gypsum, and sub-soiling + gypsum treatments compared to light harrowing + no mulch and no-tillage + no mulch treatments, respectively. Soil moisture utilization by gram and wheat was better in deep ploughing + gypsum treatments. The highest grain yields of gram (1.66t ha-1) and wheat (1.52 t ha-1) were obtained with sub-soiling + gypsum and deep ploughing + gypsum treatments. Deep village (sub-soiling and deep ploughing) and gypsum proved superior to other tillage end mulches on soil for moisture conservation, its efficient use and grain yields of the gram and wheat.